Assessment of the Quality of Life in Patients with Migraine - Pociūtė, S.; Jakavonytė-Akstinienė, A. (Neurologijos seminarai, 2023)
Introduction. Migraine is one of the most common neurological disorders in the world, affecting around 1.1 billion people worldwide. The disease impacts on both physical and mental health, while also reducing the quality of life. The aim of this study was to evaluate the quality of life of patients with migraine and its association with socio-demographic characteristics.Materials and Methods. The study was conducted between November 2023 and January 2024. A total of 370 patients with migraine took part in this study. Patients participated in an anonymous online questionnaire survey. The survey consisted of a two-part questionnaire: 1) demographic data; 2) Short Form 36 Medical Outcomes Study questionnaire (SF-36 questionnaire). Statistical analysis of the data was performed by using Microsoft Office Excel 2010 and SPSS (Statistical Package for Social Science) 24.0 software packages. The results were considered as statistically significant at p
Keywords: migraine; quality of life; SF-36